Frontiers in hemodialysis: Innovations and technological advances. Issue 2 (9th September 2020) - Basile, Carlo; Davenport, Andrew; Mitra, Sandip; Pal, Avishek; Stamatialis, Dimitrios; Chrysochou, Constantina; Kirmizis, Dimitrios
Abstract: As increasing demand for hemodialysis (HD) treatment incurs significant financial burden to healthcare systems and ecological burden as well, novel therapeutic approaches as well as innovations and technological advances are being sought that could lead to the development of purification devices such as dialyzers with improved characteristics and wearable technology. Novel knowledge such as the development of more accurate kinetic models, the development of novel HD membranes with the use of nanotechnology, novel manufacturing processes, and the latest technology in the science of materials have enabled novel solutions already marketed or on the verge of becoming commercially available. This collaborative article reviews the latest advances in HD as they were presented by the authors in a recent symposium titled "Frontiers in Haemodialysis, " held on 12th December 2019 at the Royal Society of Medicine in London.